Law, state and the agrarian question in Zimbabwe - Tshuma, Lawrence (1995)
The agrarian question is one of Zimbabwe's enduring colonial legacies. At independence the ensemble if issues comprising the agrarian question included an inequitable racial distribution of land, different tenure systems for blacks and white settlers, a discriminatory provision of agricultural support services, and repressive relations between the state and the peasantry. Peasant grievances over the agrarian question mobilised their support for the liberation struggle which culminated in independence in 1980. Contrary to the expectations of the majority of Zimbabweans, agrarian reforms introduced since independence have not transformed the colonial agrarian structure. The thesis investigates factors which account for the nature of agrarian reforms. Using a socio-historical analysis, it examines changes and continuities in agrarian policies and laws. In the main, the thesis argues that reform has been shaped by changes in power relations in society which are reflected in the exercise of state power. It shows that the manner in which independence was achieved and the character and ideologies of the social forces that inherited state power account for the changes and continuities in policies and laws. The thesis demonstrates that land reform was initially constrained by the constitutional provision which protected private property from compulsory acquisition. More important, it argues that reform has been determined by the failure to transform the inherited accumulation strategy, of which capitalist agriculture is an integral element. In addition, it demonstrates that the manner in which land has been redistributed reflects the continuation of colonial ideologies of modernisation. Furthermore, the thesis shows that communal tenure as constructed by the colonial state has been retained partly because of the ideology of nee-traditionalism and partly because it allows the state to intervene in peasant land use and production processes' as part of the process of modernisation. It also shows that the modernisation of peasant agriculture has been attempted through the extension of input, credit, price and marketing packages. Consequently, the thesis shows that the agrarian question is as relevant today as it was at independence, and that the limited and contradictory nature of the agrarian reforms reflects the limitations and contradictions inherent in the post-colonial democratisation process. Hence agrarian reform can only be adequately addressed as part of a comprehensive transformation of the accumulation process and societal democratisation.